Analysis of Student Communication in the Discovery Learning Model Using Transcript-based Lesson Analysis - Irvan Irvani, Asep; Agus, Dian (KnE Social Sciences, 2024)
This study aimed to analyze student and teacher communication in discovery learning through transcript-based lesson analysis (TBLA). The research was conducted in one of the junior high schools in Garut Regency on science subjects. The learning material studied in this research was about Coulomb’s Law. The learning video was taken from one of the open class activities from a series of lesson study activities. As many as 16 students of grade 9 were included in the study. Through descriptive research methods, researchers revealed learning trajectories and student communication methods while learning through the transcripts made. Learning activities are divided into three main parts, namely introduction, core activities, and closing. There are five stages in the core activity, namely literacy activities, critical thinking, collaboration, communication, and creativity. The results of the analysis show that in the preliminary activity, communication is dominated by the teacher. The dialogue that appears is just a minimalistic dialogue. In core activities, student communication had started to dominate, especially at the collaboration and communication stages. The use of interactive simulation media at the collaboration stage improved the communication between students. The creativity stage was mostly dominated by the teacher, until the closing activity, and less by student communication. The lag time between teacher questions and student answers is the key to student responses. When the pause is given too quickly, there was no communication from students at almost all stages. Keywords: student communication, discovery learning, transcript-based lesson